Strategic Management: Analysis of the Influence of Influence Factors on Company Performance - Mendrofa, Syah Abadi; Sihite, Toga Sehat; Asrijal, Andi; Zainurossalamia, Saida; Asnawati (PT Inovasi Pratama Internasional, 2024)
This study aims to investigate the impact of implementing strategic management on the performance of PT XYZ, an important provider of electricity services in the industry. Intense competition, dynamic changes in the business environment, and customer needs demand the adoption of effective strategies. This research employs qualitative methods and a case study approach at PT XYZ. Data were gathered through in-depth interviews with company management and analysis of internal documents, as well as direct observation of operational activities. The findings of this study demonstrate that the implementation of efficacious strategic management exerts a positive influence on the efficacy of PT XYZ. By adopting a lucid and well-defined strategy, the company is capable of optimising the utilisation of its resources, augmenting its competitive edge, and fortifying its client relationships. Furthermore, strategic management enables companies to identify and address the risks inherent to their operational activities.